Pulmonary Involvement Caused by Primary Sjogren’s Syndrome: The Pilot phase of Iran Primary Sjogren’s Syndrome Registry - Asghar Hajiabbasi; Hoorvash Ebrahimi; Irandokht Shenavar Masouleh; Samira Forouzan; Amirmohammad Ghanbari; Azita Tangestaninejad; Pooneh Ghavidel Parsa (مجله دانشگاه علوم پزشکی گیلان)
Background: Primary Sjogren's syndrome is a progressive systemic autoimmune disease involving lacrimal and salivary glands. This disease can be associated with systemic complications such as polyarthritis, autonomic dysfunction, pancreatitis, vasculitis, and kidney and lung complications. Pulmonary involvement in Sjogren's can include both airway and interstitial lung involvement. Dry trachea, interstitial lung disease, bronchitis, or lymphoma are among this disease's most common pulmonary complications. The existence of these conflicts as well as their type have a great impact on the quality of life of patients as well as their mortality rate. Objective: This study aimed to determine pulmonary involvement caused by primary Sjogren's syndrome in patients registered in the pilot phase of the national registry of primary Sjogren's syndrome. Methods: This study investigated 71 patients with a definite diagnosis of primary Sjogren's syndrome. Based on the clinical symptoms and lung specialists' opinions, the patients underwent lung imaging and lung function tests. The presence of pulmonary involvement and the effect of various factors on its presence in patients were evaluated. Results: Out of 71 studies, 69 patients had at least one of the ocular or oral symptoms of SICCA. 39 patients were positive for both anti-SSA and anti-SSB tests. 11% of patients had pulmonary involvement, and among the examined factors, only positive RF had a significant effect on the presence or absence of pulmonary involvement. Conclusion: Our results showed that in the pilot phase of this program, 95.8% of patients had positive serological results. The most common organ involved was the lung.